Comparison of the Anti-angiogenic and Anti-inflammatory Effects of Two Antibiotics: Clarithromycin Versus Moxifloxacin. (2nd April 2016) - Uehara, Hironori; Das, Subrata K.; Cho, Yang Kyung; Archer, Bonnie; Ambati, Balamurali K.
Abstract: Purpose : Clarithromycin is a 14-membered ring macrolide antibiotic with anti-inflammatory as well as antibacterial activity, and has been used worldwide. Moxifloxacin is a leading fourth generation quinolone antibiotic that has been used worldwide perioperatively. We intended to evaluate whether clarithromycin can suppress angiogenesis and inflammation in the cornea, and to compare the anti-inflammatory and anti-angiogenic effects of the two antibiotics, clarithromycin and moxifloxacin. Methods : We made a murine corneal suture model and tested the anti-inflammatory and anti-angiogenic effects of clarithromycin (5 mg/ml) and moxifloxacin (5 mg/ml) in two randomly divided groups. Dexamethasone (5 mg/ml) was used as a positive control. After making two sutures on the cornea, we performed subconjunctival injections (10 μl) on each group on the day of suture, and every day thereafter until the 8th day post-suture. After harvesting corneas on the 8th post-suture day for immunohistochemical staining, we compared neovascularization (NV), lymphangiogenesis (LY) and inflammatory cell infiltration among the groups. Results : Clarithromycin suppressed NV, LY and inflammatory infiltration, compared with phosphate-buffered saline (PBS). However, moxifloxacin did not suppress NV, LY, or inflammatory infiltration, compared with PBS. Comparison between clarithromycin and moxifloxacin, clarithromycin showed a tendency of decreasing LY ( p  = 0.063) and had less inflammatory cell infiltration ( p  < 0.05) than did the moxifloxacin group. The anti-(lymph)angiogenic and anti-inflammatory effects of clarithromycin were as high as those of dexamethasone. Conclusion : Clarithromycin suppressed LY and inflammation in the cornea, and its anti-inflammatory effect was significantly superior to that of moxifloxacin.